Spray Drying of Lactic Acid Bacteria (2019)
Lactic acid bacteria (LAB) are microorganisms used principally as a starter or probiotic cultures in food and pharmaceutical industry. The preservation of LAB by different drying methods is an interesting topic due to the increase in demand for these microorganisms. Spray drying is an effective method that allows products to be obtained at a low cost compared with lyophilization. The aim of this systematic review is to present in an organized way the scientific articles that have been published in spray drying processes with lactic acid bacteria (LAB). The methodology used in the search and selection of the articles provides an exploration during 2009-2019. The results of the different articles consulted were compared establishing the methodological similarities, the main microorganisms studied are discussed, as well as the protective agents used to improve the viability during the spray drying, conditions, and scale of the spray drying equipment, finally the characteristics of the dry products obtained. The information compiled here provides work route for adjusting methodology when spray-drying processes for LAB are proposed.